2020
DOI: 10.1002/anie.202010026
|View full text |Cite
|
Sign up to set email alerts
|

Photoassisted Selective Steam and Dry Reforming of Methane to Syngas Catalyzed by Rhodium–Vanadium Bimetallic Oxide Cluster Anions at Room Temperature

Abstract: Photoassisted steam reforming and dry (CO2) reforming of methane (SRM and DRM) at room temperature with high syngas selectivity have been achieved in the gas‐phase catalysis for the first time. The catalysts used are bimetallic rhodium–vanadium oxide cluster anions of Rh2VO1–3−. Both the oxidation of methane and reduction of H2O/CO2 can take place efficiently in the dark while the pivotal step to govern syngas selectivity is photo‐excitation of the reaction intermediates Rh2VO2,3CH2− to specific electronically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 66 publications
2
19
0
Order By: Relevance
“…This work also confirms that by selecting a suitable oxide support (e.g. TiO 2 − cluster), the single Rh atom is sufficiently active to enable the co‐conversion of methane with carbon dioxide to syngas, in sharp contrast to the VO x cluster support, for which the Rh 2 dimer is indispensible for syngas production [8d] …”
Section: Figuresupporting
confidence: 70%
See 1 more Smart Citation
“…This work also confirms that by selecting a suitable oxide support (e.g. TiO 2 − cluster), the single Rh atom is sufficiently active to enable the co‐conversion of methane with carbon dioxide to syngas, in sharp contrast to the VO x cluster support, for which the Rh 2 dimer is indispensible for syngas production [8d] …”
Section: Figuresupporting
confidence: 70%
“…An increase in the reaction temperature leads to efficient formation of methyl radicals [8c] . Very recently, selective DRM was achieved at room temperature by using Rh 2 VO 1‐3 − anions in combination with photoirradiation to produce the second H 2 and CO molecules [8d] . Herein, we demonstrate that RhTiO 2 − co‐converts CH 4 and CO 2 to 2 H 2 +CO at room temperature without photo‐irradiation.…”
Section: Figurementioning
confidence: 76%
“…Shoji et al [133] reported a SrTiO 3 -supported Rh catalyst for UV-light-driven CO 2 reduction with CH 4 reforming, which cannot be realized by traditional thermal catalysis. The photogenerated h + and ewere employed for the oxidation of CH 4 over SrTiO 3 and the reduction of CO 2 over Rh, respectively.…”
Section: Nitride-based Photocatalystsmentioning
confidence: 99%
“…Among them, the strategies of CO 2 reduction to produce solar fuels using inexhaustible solar energy are attractive as the two major global issues could be simultaneously tackled. The strategies involve photocatalytic CO 2 reduction by H 2 O [ 1–25 ] and organic compounds (e.g., triethanolamine, CH 4 ) as electron donors, [ 26–34 ] light‐driven thermochemical splitting of CO 2 , [ 35–40 ] photothermocatalytic CO 2 reduction by H 2 O, [ 41–45 ] H 2 , [ 46–50 ] and CH 4 (photothermocatalytic CO 2 reduction by CH 4 (CRM): CO 2 + CH 4 = 2CO + 2H 2 , Δ H 298 = 247 kJ mol −1 ). [ 51–59 ] For the potential application of the strategies, high fuel production rate ( r fuel ), large light‐to‐fuel efficiency ( η ), and excellent durability are prerequisite.…”
Section: Introductionmentioning
confidence: 99%
“…The photocatalytic strategies using semiconductor photocatalysts has the advantage of operating at ambient temperature, but low r fuel and η are two major obstacles to be overcome due to the recombination of the majority of the photogenerated chargers and the difficult in the utilization of infrared energy in solar light. [ 1–34 ] Photothermocatalytic CRM is very promising as both r fuel and η could be simultaneously achieved. [ 53–57 ] The main catalysts for photothermocatalytic CRM reported are supported group VIII metal nanoparticles (e.g., Pt, Rh, Ru, Ni, Co, etc.)…”
Section: Introductionmentioning
confidence: 99%